2020
DOI: 10.1111/1758-5899.12783
|View full text |Cite
|
Sign up to set email alerts
|

Acknowledging Urbanization: A Survey of the Role of Cities in UN Frameworks

Abstract: Cities are playing an increasingly vital role in global sustainability. Yet there is still little systematic and international evidence on the recognition and formal role of cities in multilateral affairs. Where and how are cities acknowledged as part of global efforts? How do the United Nations frame this 'urban' contribution to major international processes and agendas? To offer some initial evidence-based pointers to this set of problems, we present an analysis of explicit references to cities in major UN f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
(53 reference statements)
0
11
0
3
Order By: Relevance
“…In today's world, we have concrete evidence of the ascent of cities as international actors (Thouez, 2020; see also Acuto & Leffel, 2020; Kosovac et al., 2020). Scholarship has called attention to this fact over the last 2 decades (Bulkeley & Betsill, 2013; Gleeson, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In today's world, we have concrete evidence of the ascent of cities as international actors (Thouez, 2020; see also Acuto & Leffel, 2020; Kosovac et al., 2020). Scholarship has called attention to this fact over the last 2 decades (Bulkeley & Betsill, 2013; Gleeson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The legacy of Saskia Sassen's (1991Sassen's ( , 1995Sassen's ( , 2002 global city thesis for scholars of global and urban studies alike, is to understand the impact of global processes on the social structure of cities. Situated in this growing body of work is a pressing need for more systematic investigations of emerging 'global urban governance' across various and increasingly intersecting policy domains (Acuto & Leffel, 2020;Kosovac et al, 2020). Some have famously suggested that mayors should replace statesmen brokering inter-state relationships and leading international cooperation across borders (Barber, 2013;Hachigian, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, urbanization has swept the world and become one of the most remarkable phenomena in the process of global modernization [1]. As the largest developing country in the world, China has experienced long-term and sustained ultra-high speed economic growth and large-scale urbanization since the implementation of reform and opening up in 1978 [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Recente levantamento sobre as menções às questões urbanas em documentos oficiais da ONU apresenta considerável aumento a partir de 1996 (Kosovac et al, 2020). Contudo, a maior quantidade de menções na temática urbana refere-se à ideia 'desenvolvimento'.…”
Section: A Promessa De Justiça Por Um Urbano Salutarunclassified
“…A predominância do 'desenvolvimento', em detrimento de referências específicas à 'habitação' e 'igualdade' por exemplo, perigosamente abarca desde atenuação da pobreza e melhorias na qualidade de vida em cidades e comunidades sustentáveis, como previsto no 11º objetivo da Agenda 2030, até o desenfreado desenvolvimento econômico capaz de atrair maior circulação de capital e fazer girar a roda cíclica de humilhação e espoliação social como vimos nos Campos Elíseos. Desta forma, o aumento de menções sobre as cidades no debate das Organização das Nações Unidas pouco avança em transformações práticas significativas nas relações de poder entre países e cidades, perpetuando incertezas sobre a concepção de cidade e os impactos das transformações destas na vida das pessoas (Kosovac et al, 2020). As cidades adotam a impiedosa estratégia de eliminar a pobreza por meio do lucro (Rolnik, 2015) justamente em cima dos mais pobres, e são descaracterizadas junto às injustiças que compõem o pacote dos projetos urbanísticos de requalificação urbana na América Latina.…”
Section: A Promessa De Justiça Por Um Urbano Salutarunclassified